Influence of the ICDAS e-learning program for occlusal caries detection on dental students - Diniz, Michele B.; Lima, Luciana Monti; Santos-Pinto, Lourdes Aparecida Martins dos [UNESP]; Eckert, George J.; Zandoná, Andrea G. Ferreira; Cordeiro, Rita da Cássia Loiola (My University, 2010)
The aim of this study was to evaluate the influence of ICDAS training in a group of dental students for occlusal caries detection in permanent teeth. Premolars and molars (N=104) with occlusal surfaces varying from ICDAS scores 0 to 6 were cleaned, one occlusal site per tooth was selected, and a photograph taken to identify the site. Eight senior dental students examined the teeth twice with a one-week interval between examinations during each of two phases: before and after the ICDAS e-learning program. Teeth were histologically assessed for caries extension. Intraclass correlation coefficients for intra- and interexaminer repeatability were high, both before (0.75 and 0.72, respectively) and after e-learning (0.82 and 0.78, respectively). The ICDAS scores decreased significantly from before to after e-learning (p=0.0001). Correlation between ICDAS scores and histology scores was moderate (0.57 before e-learning and 0.61 after). Although the ROC curve shows an improvement in the use of the ICDAS scoring after e-learning, the difference was not significant (p=0.10). Specificity of the ICDAS scores significantly improved after e-learning (77 percent vs. 36 percent), and sensitivity was reduced slightly after e-learning (87 percent vs. 92 percent). The ICDAS e-learning program improved the performance of the diagnostic skills of the investigated students for the detection of occlusal caries lesions.
Keywords: Dental caries; Dental education; Educational methodologies; Oral diagnosis